Influence of the breed of bull (Bos taurus indicus vs. Bos taurus taurus) and the breed of cow (Bos taurus indicus, Bos taurus taurus and crossbred) on the resistance of bovine embryos to heat - Eberhardt, Bruno G. [UNESP]; Satrapa, Rafael A. [UNESP]; Capinzaiki, Claudia R. L. [UNESP]; Trinca, Luzia A. [UNESP]; Barros, Ciro M. [UNESP] (Elsevier B.V., 2009)
In vitro studies have shown that Bos taurus indicus (B. t. indicus) embryos submitted to heat shock at early stages of development are better able to survive as compared to Bos taurus taurus embryos. Embryo genotype influences resistance to heat shock thus leading to the question as to whether embryos sired by thermo-tolerant breeds exhibit the same resistance to heat shock. In the present study the influence of both oocyte and semen, on the resistance to heat shock (HS) at early stages of in vitro development, was assessed in B. t. indicus [Nelore (N) breed], B. t. taurus [Holstein (H) and Angus (A) breeds] and crossbreds. In Experiment 1, Nelore and crossbred oocytes were collected from slaughterhouse ovaries and fertilized with spermatozoa from Nelore and Angus bulls. Presumptive embryos were collected and randomly assigned to control (39 degrees C) or HS at 12, 48 or 96 h post insemination (hpi; 41 degrees C for 12 h) treatments. The cleavage rates and proportion of embryos developing to the blastocyst and hatched blastocyst stages were recorded on Days 2, 8 and 10, respectively. Heat shock treatment decreased development of both Nelore and crossbred embryos. There was a significant interaction between time (12, 48 or 96 hpi) and temperature for blastocyst rates, i.e., the embryos became more thermotolerant as development proceeded. In Experiment 2, oocytes from Nelore and Holstein cows were fertilized with semen from bulls of either Nelore or Angus breeds, and subjected to 12 h HS at 96 hpi. Heat shock at 96 hpi, decreased embryo development. Additionally, cow x treatment and bull x treatment interactions were significant for blastocyst rates, i.e., both breed of cow and breed of bull affected the decline in blastocyst rate caused by heat shock treatment. In conclusion, the present results indicate that Nelore embryos (indicus) are more resistant to heat shock than Holstein (taurus) at early stages of in vitro development, and that embryos become more thermo-tolerant as development proceeds. Additionally, the resistance to heat shock was a result of the genetic contribution from both oocyte and spermatozoa. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Cattle-embryo; Heat shock; In vitro fertilization; Bos taurus taurus; Bos taurus indicus